PENERAPAN STRATEGI MANAJEMEN KELAS PARTISIPATIF UNTUK MENINGKATKAN KETERLIBATAN SISWA DALAM PEMBELAJARAN IPA MATERI KELESTARIAN LINGKUNGAN DI SEKOLAH DASAR - Yani, Fitri; Elizar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low student engagement in science learning on environmental sustainability material in Grade IV of SD Negeri 02 Kota Alam is indicated by passive students, low confidence, and teacher-dominated instruction. The purpose of this study is to describe the implementation of participatory classroom management strategies in improving student engagement. This research used a descriptive qualitative approach with data collection techniques including observation, interviews, and literature study. The research subjects were the fourth-grade teacher and students. The results show that the teacher has implemented participatory classroom management strategies through group discussions, question and answer activities, collaboration, and providing opportunities for students to express their opinions, thereby leading the learning process toward student-centered learning. However, student engagement is still not optimal, as some students remain passive and less active. This condition is influenced by internal factors such as motivation and academic ability, as well as external factors such as time management and instructional strategies. In addition, learning has not fully reached the principles of deep learning because it is still at the basic thinking level. In conclusion, the implemented strategy has been carried out but needs strengthening through learning models such as Problem Based Learning (PBL) and Project Based Learning (PjBL) to make student engagement more active and meaningful.